Pneumoperitoneum, pneumatosis intestinalis and portal venous gas: Rare gastrostomy complications case report. (2019) - Perez Rivera, Carlos Jose; Ramirez, Nathaly Alexandra; Gonzalez-Orozco, Alejandro; Caicedo, Isabella; Cabrera, Paulo
Highlights: Open gastrostomy lethal complications include intestinal pneumatosis and portal venous gas. Intestinal necrosis, disruption of mucosa, increased permeability of mucosa, and pulmonary disease, can cause complications. There are several theories describing pathophysiology of intestinal pneumatosis. one of them, secondary to surgery or trauma. Medical versus surgical management of the complications depend on the patient's comorbidities and physician's consideration. Abstract: Introduction: The gastrostomy is one of the most common procedures performed in general surgery. Although a simple procedure, it is not exempted from potential complications, specifically portal venous gas and intestinal pneumatosis being some of the ones with higher rates of mortality. The following case report presents a pneumoperitoneum due to extensive pneumatosis from esophageal, gastric, intestinal and portal gas. These rare complications were managed medically without undergoing emergency surgical intervention. Presentation of Case: A 19-year-old male patient, with previous history of cerebral palsy, chronic malnutrition and severe physical deconditioning, required a nutritional access. Due to co-existing pathologies, an open gastrostomy was chosen as the best intervention, which was performed without complications. On the tenth postoperative day, patient presents abdominal pain and diarrhea; laboratory results were within normal limits, and the abdominal computed tomography scan reported extensive pneumatosis compromising esophagus, stomach, small intestine, part of the colon, pneumoperitoneum and gas in the portal venous system. Medical management was carried out with an adequate recovery. Discussion: Intestinal pneumatosis and portal venous gas are rare and potentially lethal complications. Surgical intervention as well as severe malnutrition impairs carbohydrate digestion and promotes bacterial fermentation forming large volumes of gas and dissection of the intestinal mucosal wall, causing the intestinal pneumatosis evidenced in this case report. Conclusions: This case report presents a rare open gastrostomy complication, as well as a differential diagnosis to pneumoperitoneum. Additionally, the medical management poses a successful alternative to an emergency surgical intervention.